Hanbury-Brown-Twiss interferometry for sonoluminescence bubble - Hama, Y.; Kodama, T.; Padula, S. S. (American Physical Soc, 1997)
Two-photon correlation of the light pulse emitted from a sonoluminescence bubble is discussed. It is shown that several important features of the mechanism of light emission, such as the time scale and the shape of the emission region, could be obtained from Hanbury-Brown-Twiss interferometry. We also argue that such a measurement may serve to reject one of the two currently suggested emission mechanisms, i.e., the thermal process versus the dynamical Casimir effect.